Material Religion in Modern Britain
XIII, 240 p.
Keywords: This volume contributes towards to developments in the study of religion that illuminate the plural nature of religious change in modern Britain. It makes a critical intervention in British studies of religion by bringing the analytical insights of material culture, to bear on religion in the British World.